A high-status Anglo-Saxon settlement at Flixborough, Lincolnshire - Loveluck, C. P.
Excavations at Flixborough, Lincolnshire (1989Ð91) revealed an important Anglo-Saxon settlement. Here the various interpretations are discussed, ranging from monastic to 'magnate'.